The performance level of MSMEs stimulated by an entrepreneurial mindset, networking capability, and digital marketing innovation - Primadona; Emrizal (Heritage and Sustainable Development)
This study aims to examine the influence of entrepreneurial mindset, digital marketing innovation, and networking ability on business performance using competitiveness as a moderating variable in micro, small, and medium enterprises (MSMEs) in Indonesia. This study uses a quantitative approach to examine the relationship between the variables studied in this study specifically for MSMEs. Data collection uses a questionnaire with a survey method, with the unit of analysis being MSME owners. A total of 100 MSME owners were asked for information to confirm the research objectives. Data processing uses SEM with PLS applications. The results of the study reveal that all exogenous variables, such as entrepreneurial mindset, Digital Marketing Innovation, and Networking Ability, have a positive and significant effect on the endogenous variable, namely business performance, which is moderated by the competitiveness variable. MSMEs need to make new discoveries that are different from other MSMEs and have something that competitors do not have in order to increase their competitiveness, especially in developing countries. The limitation of this study is that it still uses 100 respondents with the competitiveness variable as a moderating variable. Future research can add other variables, such as entrepreneurial resilience, as a moderating variable in viewing business performance.